Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

I want to find the Laplace transform of the following signal but I don't know what to do with the absolute value.

$$x(t)=e^{-|t|}\; u(t+1)$$

The first thing it came to my mind is to split in negative and positive sides and then find each one and add them. The problem is that I checked back to the solutions and it not the same.

Any ideas?

share|improve this question
    
Isn't $|-t|=|t|$ for all $t$? –  Babak S. Jun 25 '12 at 20:02
    
@BabakSorouh I fixed it. Thanks. –  jeanleauveux22 Jun 25 '12 at 20:04
    
What LT are you considering? Two sided? –  Pedro Tamaroff Jun 25 '12 at 20:15
    
@PeterTamaroff Yes two sided. –  jeanleauveux22 Jun 25 '12 at 20:17

2 Answers 2

up vote 1 down vote accepted

Since you're considering the two sided Laplace Transform you need to evaluate

$$\mathcal L(s)=\int_{-\infty}^\infty e^{-|t|} \theta(t+1) e^{- st}dt$$

Since $\theta(t+1)=0$ for $t<-1$ you integral becomes

$$\mathcal L(s)=\int_{-1}^\infty e^{-|t|} e^{- st}dt$$

Now we consider that for $(-1,0)$, $-|t|=t$, and for $(1,\infty)$, $-|t|=-t$, so that

$$\mathcal L(s)=\int_{-1}^0 e^{t} e^{- st}dt+\int_{1}^\infty e^{-t} e^{- st}dt$$

Can you take it from there?

share|improve this answer
    
Yes I understand. What's different with the right sided LT? –  jeanleauveux22 Jun 25 '12 at 20:31
    
@jeanleauveux22 The "right" sided is usually called "one sided" and is $\mathcal L(s) =\int_0^\infty \theta(t)f(t) e^{-st}dt$ where $\theta$ is the Heaviside step function. –  Pedro Tamaroff Jun 26 '12 at 0:15

$$ e^{-|t|} = e^{t}u(-t)+e^{-t}u(t) $$ $$ x(t)=e^{-|t|} u(t+1)=e^{t}[u(t+1)-u(t)]+e^{-t}u(t) $$ Two Side Laplace Transform : $$ X(S)= \int_{-\infty}^{\infty} x(t)e^{-st}dt $$ $$ X(S)=\int_{-1}^0 e^t e^{-st}dt + \int_0^{\infty} e^{-t} e^{-st}dt $$ $$ X(S)=\int_{-1}^0 e^{-(s-1)t}dt + \int_0^{\infty} e^{-(s+1)t}dt $$ $$ X(S)= \frac{-1} {s-1}e^{-(s-1)t} |_{-1}^0 + \frac{-1} {s+1}e^{-(s+1)t}|_0^{\infty} $$ $$ X(S)=\frac{-1+e^{s-1}} {s-1} +\frac{1} {s+1} $$

share|improve this answer

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.